A protocol for distilling animal body water from biological samples and measuring oxygen and hydrogen stable isotopes via cavity ring-down spectroscopy - Steele, Zachary T.; Caceres, Karen; Jameson, Austin D.; Griego, Michael; Rogers, Elizabeth J.; Whiteman, John P. (Isotopes in environmental and health studies, 2024)
The application of stable isotope analysis (SIA) to the fields of ecology and animal biology has rapidly expanded over the past three decades, particularly with regards to water analysis. SIA now provides the opportunity to monitor migration patterns, examine food webs, and assess habitat changes in current and past study systems. While carbon and nitrogen SIA of biological samples have become common, analyses of oxygen or hydrogen are used more sparingly despite their promising utility for tracing water sources and animal metabolism. Common ecological applications of oxygen or hydrogen SIA require injecting enriched isotope tracers. As such, methods for processing and analyzing biological samples are tailored for enriched tracer techniques, which require lower precision than other techniques given the large signal-to-noise ratio of the data. However, instrumentation advancements are creating new opportunities to expand the applications of high-throughput oxygen and hydrogen SIA. To support these applications, we update methods to distill and measure water derived from biological samples with consistent precision equal to, or better than, ± 0.1 ‰ for δ 17 O, ± 0.3 ‰ for δ 18 O, ± 1 ‰ for δ 2 H, ± 2 ‰ for d-excess, and ± 15 per meg for Δ 17 O.